(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2025)
In order to improve the wettability of sintering dust, we investigated the action mechanism of Triton X-100 (TX-100), which synergizes with Dodecyl Trimethyl Ammonium Bromide (DTAB). The settling times of nine different types of surfactants were measured, and the optimal ratio of cationic and nonionic surfactants to synergistically improve the wettability of sintering dust was determined from these measurements. The adsorption performance of the surfactants in the mixed solution and their effect on the wetting properties of sintering dust were investigated by sedimentation test, adsorption amount, Fourier transform infrared spectroscopy, and zeta potential determination. The results showed that a synergistic effect could be obtained when DTAB and TX-100 were mixed, and the DTAB: TX-100=2:2 composite solution with a concentration of 0.3% had a good wetting effect on the sintering dust. As the concentration of the surfactant mixtures increased, the content of hydrophilic functional groups and the absolute potential value of the surface of the sintering dust increased accordingly. Among them, DTAB was affected by alkyl interactions and had a greater adsorption affinity, and the hydrophobic tail of TX-100 was entangled with that of DTAB due to hydrophobic interactions and shared an adsorption site. This study contributes to the selection of surfactants for the efficient wetting of sintering dust and provides a theoretical basis for hydrometallurgy and dust control.